2017
DOI: 10.1038/ncomms14532
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence mediates fibrotic pulmonary disease

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease characterized by interstitial remodelling, leading to compromised lung function. Cellular senescence markers are detectable within IPF lung tissue and senescent cell deletion rejuvenates pulmonary health in aged mice. Whether and how senescent cells regulate IPF or if their removal may be an efficacious intervention strategy is unknown. Here we demonstrate elevated abundance of senescence biomarkers in IPF lung, with p16 expression increasing with disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
1,153
3
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,149 publications
(1,271 citation statements)
references
References 47 publications
51
1,153
3
5
Order By: Relevance
“…However, senescent cells secrete TGFβ1 capable of inducing α‐SMA expression in a paracrine manner, as a specific inhibitor of TGF‐β receptor I suppressed the ability of senescent cell conditioned medium to induce α‐SMA expression in human fibroblasts (Supporting Information Figure S3k). These data suggest that senescent cells can promote myofibroblast transdifferentiation through their SASP, which is consistent with a recent study (Schafer et al, 2017). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, senescent cells secrete TGFβ1 capable of inducing α‐SMA expression in a paracrine manner, as a specific inhibitor of TGF‐β receptor I suppressed the ability of senescent cell conditioned medium to induce α‐SMA expression in human fibroblasts (Supporting Information Figure S3k). These data suggest that senescent cells can promote myofibroblast transdifferentiation through their SASP, which is consistent with a recent study (Schafer et al, 2017). …”
Section: Resultssupporting
confidence: 93%
“…While the formation of myofibroblasts during wound healing in a mouse model system was reported to be stimulated by SASP factors secreted from senescent fibroblasts and endothelial cells generated at the site of injury (Demaria et al, 2014), other studies demonstrated that, paradoxically, the SASP causes bystander senescence in somatic human fibroblasts (Acosta et al, 2013; Hubackova et al, 2012; Nelson et al, 2012). Recent studies, however, have raised the possibility that the SASP can promote development of myofibroblasts, as fibroblast incubated with conditioned medium from senescent cells develop into contractile α‐SMA‐expressing cells (Schafer et al, 2017). Although it is possible that different senescence‐inducing signals activate the production of distinct senescence‐associated secretomes that may either trigger a transdifferentiation program or alternatively, bystander senescence in human fibroblasts, our results demonstrate that these two events are similar.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by recent studies demonstrating that the genetic clearance of SCs prolongs the lifespan of mice and delays the onset of several age‐related diseases and disorders in both progeroid and naturally aged mice (Baker et al., 2011, 2016). Therefore, the pharmacological clearance of SCs with a small molecule, a senolytic agent that can selectively kill SCs, is potentially a novel anti‐aging strategy and a new treatment for chemotherapy‐ and radiotherapy‐induced side effects (Baar et al., 2017; Chang et al., 2016; Childs et al., 2016; Demaria et al., 2017; Jeon et al., 2017; Ogrodnik et al., 2017; Pan et al., 2017; Schafer et al., 2017; Yosef et al., 2016; Zhu et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The targeting of senescent cells through a semi‐genetic approach extends the health span by ameliorating the aging‐associated phenotypes of kidney, eye, heart, bone, and lung tissues in wild‐type or progeria model mice (Baar et al, 2017; Baker et al, 2016; Farr et al, 2017; Hashimoto et al, 2016). In addition, senescent cell elimination alleviates pathologies in disease models, which include those of atherosclerosis, idiopathic pulmonary fibrosis (IPF), hepatic steatosis, and osteoarthritis (Childs et al, 2016; Jeon et al, 2017; Ogrodnik et al, 2017; Schafer et al, 2017). As the removal of senescent cells has beneficial effects on the maintenance of tissue homeostasis and the prevention of diseases in mice, senescent cells are expected to have potential as therapeutic targets for these diseases.…”
Section: Introductionmentioning
confidence: 99%